Dynamics and Direction of Gig Economy Research Development 2015–2025: Bibliometric Analysis and Its Implications for Labor Protection in the Digital Age - Naibaho, Novita Dolores; Wulandari, Wida (Journal of Economics and Management Scienties, 2025)
The gig economy has become a central element in the transformation of the global labor market, particularly with the rapid growth of digital technology and online platforms. This study aims to map the dynamics and research trends on the gig economy over the last decade (2015–2025) through a bibliometric approach based on 328 selected articles from the Scopus database. The data were obtained through a systematic screening process of peer-reviewed journal articles published in English within the specified period. Bibliometric analysis was carried out using the Bibliometrics R-package, which involved descriptive statistics, co-authorship networks, co-occurrence mapping, and thematic clustering. The results indicate a sharp increase in publications after the COVID-19 pandemic, shifting research from conceptual discussions to critical issues such as labor protection, algorithmic management, and social inequality. The thematic analysis identifies four main clusters: regulation and worker protection, algorithmic management, innovation and digital economic growth, and human values in digital labor. This study highlights research gaps in employment policy, algorithm governance, and digital inclusion, especially in developing countries, and contributes to both theoretical development and policy design in line with Sustainable Development Goals (SDG 8 and SDG 10).